Structuring and standardisation of vocational orientation : Evaluation-based design of a central action area for vocational education and training - Kunert, Carolin [Verfasser]; Kirst, Guido [Verfasser] (My University, 2019)
"Using the example of the BMBF programme 'Supporting vocational orientation in inter-company vocational training centres and comparable VET centres' (BOP), this article explores the question of what a funding programme can contribute to the development of a central action area for VET, and the importance of a supporting evaluation in this context. The key data of the programme and evaluation are outlined in the introduction, and the article concludes with the presentation of the most significant outcomes of the evaluation and the consequences of these for the shaping of vocational orientation." (Author's abstract ; BIBB-Doku)
Strukturierung und Standardisierung der Berufsorientierung
Keywords: L 5 Beratung & Orientierung; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; S 3.3.4 Überbetriebliche Bildungsstätten (ÜBS); L 6.2.3 Evaluation; Berufsorientierung; Berufswahl; Überbetriebliche Berufsbildungsstätte; Förderprogramm; Evaluation